Comportamento alimentar do Petrel-Gigante-do-Sul na Antártica: seleção de habitat, variação individual e efeitos da personalidade - Finger, Júlia Victória Grohmann (Universidade do Vale do Rio dos Sinos, 2023)
The intraspecific variability in the foraging behavior of seabirds is a known fact. In addition to variations associated with sex, morphological classes or age, it is common for individuals to specialize their feeding behavior to varying degrees, some being highly faithful to specific areas and consistent in their foraging strategies. Individual variation in foraging can have important implications for the species. Recent studies indicate that animal personality – consistent individual variation in behavioral traits, e.g. boldness or aggression – can lead individuals to differ in their foraging behavior. The overall goal of this thesis was to investigate sexual and individual differences in habitat selection and foraging behavior of southern giant petrels(Macronectes giganteus) and the effects of personality on these patterns. The giant petrel population studied here breeds on Nelson Island, in the maritime Antarctic. GPS tracking devices were used to investigate the breeding distribution and fine-scale foraging behavior of 67 individuals throughout the 2019/2020 and 2021/2022 breeding seasons. The behavioral test “response to a novel object” was also applied to define the personality of tracked individuals, based on their level of boldness. Step-selection functions were used to investigate which environmental variables determine foraging habitat selection, analysis of repeatability and Bhattacharyya affinity indexes were used to investigate consistency in metrics and foraging areas throughout breeding, respectively. The population was also constantly monitored to identify potential opportunistic feeding behaviors. Giant petrels showed a wide spatial distribution during reproduction. Females foraged along the entire western Antarctic Peninsula while males were concentrated along the northwest coast. Proximity to penguin colonies strongly influenced foraging habitat selection for males, while for females, water column depth was more important. Both sexes overlapped their distribution with fishing areas in Antarctica and females, in particular, used areas with fishing effort on the continental shelf of Patagonia Argentina. The population showed average consistency in foraging areas between trips, as well as in the maximum distance and duration of foraging trips. Despite the existence of interindividual personality variation, it did not influence the consistency of foraging areas, nor the metrics of trips. The main source of variation was in terms of breeding stage and sex. Intergenerational cannibalism and coprophagy of Weddell seal feces were recorded for the first time for the species. The first behavior, expressed only by males, was possibly the result of individual specialization in this resource. The second, expressed by both females and males, occurred mainly after long incubation shifts, probably to quickly recover from fasting before a long feeding trip. Due to its wide distribution in the Antarctic Peninsula, a selection of habitat associated with varied marine zones, penguin colonies, seal resting areas and fishing activities, the species is configured as an important platform to monitor isolated populations and activities. illegal fishing in and out of Antarctica.
Keywords: Distribuição reprodutiva; Seleção de habitat; Consistência individual; Canibalismo; Coprofagia; Breeding distribution; Habitat selection; Individual consistency; Cannibalism; Coprophagy; ACCNPQ::Ciências Biológicas::Biologia Geral